Facial Segmental Infantile Haemangioma: A Cutaneous Mosaicism Quandary - Vignesh Naryanan; Rahul Mahajan; Raihan Ashraf; Apoorva Sharma; Brij Lal; Dipankar De; Sanjeev Handa (Wolters Kluwer Medknow Publications, 2024)
Mosaicism has long been considered the underlying mechanism of segmental infantile hemangiomas (SIH). This was a prospective pilot case-control study conducted with the objective to quantify the percentage overlap of silhouettes of facial SIH with those of Blaschko lines (the most well studied archetypical pattern of mosaicism on face) as compared to other mosaic disorders on face.Lesional silhouettes of 8 patients with SIH (Group A) and 6 patients with other facial dermatosis known to have blaschkoidal distribution (Group B), were overlapped on a standardized template with Blaschkoidal lines on the frontal view of face. The alignment was done via the auto align tool of Photoshop and the percentage of overlap was calculated with an online image comparison software (IMGonline.com.ua). There was a significant difference in mean overlap in Group A (72.92 ± 15.6 %) as compared to Group B (90.1 ± 4.3%; P=0.018). Hence, we concluded that facial SIH do not follow lines of Blaschko.